Use of Social Media Platforms as a Key Element of Brand Marketing Strategies - Tregub, Angelina Mykhailivna; Khurdei, Viktoriia; Pushkar, Tetiana; Kuzmenko, Hanna; Bessarab, Anastasiia (Інститут економічних питань, 2023)
This article delves into the exploration of social media platforms as crucial components of brand marketing strategies. It characterizes the essence of social media platforms, emphasizing the significance of social networks within this context. The primary objectives of brand strategies, specifically those deployed on social media, are explicated. Contemporary brand strategies employed on social media platforms are elucidated. The study also scrutinizes the distinct features of brand marketing strategies utilized for positioning within social networks. This research aims to unveil the intricacies surrounding the utilization of social media platforms as pivotal elements within brand marketing strategies. The object of this study centers on social media platforms functioning as integral components of the virtual environment. The research employs various methodologies, including description, analysis, synthesis, comparison, generalization, and content analysis, to achieve comprehensive insights into the subject matter. This article focuses on the examination of social media platforms as vital elements within brand marketing strategies. To fulfill the objectives of this study, an exploration is conducted on the role of social media platforms in individuals’ lives, encompassing the essence of social networks and the positioning of brand promotion within their life cycle. Additionally, the article characterizes the business opportunities arising from the integration of social media platforms as components of marketing strategies. This paper provides an in-depth examination of the advantages and disadvantages associated with leveraging social media platforms for brand promotion. It defines contemporary strategies adopted by brands on social media platforms. Additionally, the research sheds light on the pivotal role of targeting within the realm of brand promotion.

Ця стаття присвячена дослідженню платформ соціальних медіа як важливих компонентів стратегій маркетингу брендів. Вона характеризує суть платформ соціальних медіа, підкреслюючи значення соціальних мереж у цьому контексті. Основні цілі стратегій брендів, зокрема тих, що розгортаються в соціальних мережах висвітлюються також сучасні стратегії брендів, які використовуються на платформах соціальних мереж Уважно вивчає особливості маркетингових стратегій брендів, які використовуються для позиціонування в соціальних мережах. Метою цього дослідження є виявлення тонкощів використання платформ соціальних медіа як ключових елементів маркетингових стратегій брендів компоненти віртуального середовища використовують різні методології, включаючи опис, аналіз, синтез, порівняння, узагальнення та аналіз контенту. уявлення про предмет. Ця стаття присвячена розгляду платформ соціальних медіа як життєво важливих елементів маркетингових стратегій бренду. Для досягнення цілей цього дослідження було проведено дослідження ролі платформ соціальних медіа в житті людей, охоплюючи сутність соціальних мереж і позиціонування просування бренду в їхньому життєвому циклі. Крім того, стаття характеризує бізнес-можливості, що виникають внаслідок інтеграції платформ соціальних медіа як компонентів маркетингових стратегій. У цьому документі детально розглядаються переваги та недоліки, пов’язані з використанням платформ соціальних мереж для просування бренду. Він визначає сучасні стратегії, прийняті брендами в соціальних мережах. Крім того, дослідження проливає світло на ключову роль таргетингу в сфері просування бренду.
Keywords: Brand; Visitor; Instagram; User; Marketing; Promotion; Social media platform; Social network; Strategy; Facebook; Бренд; Відвідувач; Instagram; Користувач; Маркетинг; Просування; Платформа соціальних медіа; Соціальна мережа; Стратегія; Facebook